An observational efficacy and safety analysis of the treatment of acute invasive aspergillosis using voriconazole - Jacobs, F. (Springer-Verlag, 2011)
The purpose of this study was to evaluate efficacy and safety of voriconazole in patients with acute invasive aspergillosis (IA) in a real-life, clinical setting. This was a multicenter observational study in adult patients treated with voriconazole for invasive mycosis. The study evaluated clinical response, mortality, use of other licensed antifungal therapy (OLAT), and treatment duration. This sub-analysis evaluated treatment and outcome data specifically from adult patients with proven/probable IA, while safety data were assessed in patients with proven/probable/possible IA. Of the 141 patients enrolled, 113 were adults with proven/probable IA and six had possible IA. Voriconazole treatment duration ranged from 1 to 183 days (median, 49.5 days). Voriconazole was used exclusively in 64% (72/113) of patients and in combination/sequentially with OLAT in 36%. Overall successful treatment response was 50% (57/113 patients). Twelve percent (14/113) of patients were switched to OLAT, either because of insufficient response (four patients) or for safety reasons (10 patients). Overall and attributable (entirely or partially due to fungal infection) mortality rates were 52% (59/113) and 17%, respectively. Treatment-related adverse events were reported for 18% (22/119) of patients. This observational study confirms the results of previous clinical trials demonstrating voriconazole as an effective and safe agent for treatment of confirmed acute IA.